Otorhinolaryngology, Head and Neck Surgery Services in Khartoum State in Sudan 2015 - Malik, Dr. Malik Ibrahim; Omer Ahmed, Dr. Sharfi Abdelgadir; Abdulrahim, Dr. Muna Ahmed (International Journal of Innovative Research in Medical Science, 2016)
Background: In Khartoum state, formal health services are heavily centralized. This is reflected by a specialist services coverage that is double the national ratio in Sudan, as is the case for other health services and cadres. Objectives: The aim of this study to establishment a database for ENT, audiology and speech therapy services in Khartoum state. Methods: This is descriptive, cross-sectional study hospital based. Include all Hospitals that provide otorhinolaryngological, head and neck surgery services within Khartoum state. Results: Total numbers of hospitals included in this study were 16 hospitals and departments providing otorhinolaryngological services in Khartoum state. General hospitals that contain ENT departments were 13 hospitals (81.25%) and hospitals that specialized for otorhinolaryngological services were three hospitals (18.75%). Conclusion: Otorhinolaryngological hospitals are distributed within Khartoum state with inequality to proportion of populations within provinces, also there is great deficiency on audiology and speech therapy services with variable distribution.